A pond water use planning tool for integrated farming in an alternating wet–dry season tropical climate. (1st June 2014) - Sukchan, U.; Oda, M.; Caldwell, J. S.; Taweekul, K.; Suphanchaimat, N.; Chongpraditnun, P.
A tool was developed for farmers to estimate water volume in farm ponds and plan pond water use for dry-season crop and animal production leaving adequate reserve water for rice at the start of the wet season. The tool is used to determine pond water volume at the start of the planning cycle; to determine the quantity of pond reserve water desired at the end of the planning cycle; to determine pond water evaporation during the planning period; to determine expected water consumption by desired crops and cattle; and to adjust water use if the remaining water predicted by the tool is less than the desired reserve quantity. Water use based on plans made with the tool by ten farmers was monitored from 29 December 2008 to 5 October 2009. The tool was more accurate in predicting reserve water when no rainfall added water into farm ponds, and less accurate when rainfall added water to the ponds. Prediction of reserve water in the upper paddy topographical position was more accurate compared with lower paddy and upland positions. The tool is most appropriate for dry-season diversification in upper paddy topographical positions where many new ponds have been constructed during the past twenty years.